Effects of Different Over – the - Counter Whitening Products on the Microhardness, Surface Roughness, Color and Shear Bond Strength of Enamel - Esra Yildirim; Uzay Koc Vural; Filiz Yalcin Cakir; Sevil Gurgan (Acta Stomatologica Croatica, 2022)
Objective: The purpose of this in vitro study was to evaluate the effects of four over-the-counter (OTC) whitening products on the microhardness, surface roughness, color, shear bond strength (SBS) and surface charecteristics of human enamel compared with a product used for dentist-su-pervised home whitening. Material and methods: Seventy eight enamel specimens allocated into 6 groups (n=13): 1-Opalescence PF 10% (OP) dentist prescribed home whitening product, 2-Opalescence Go prefilled tray (PT), 3-Opalescence Whitening Toothpaste (WT), 4-Listerine Healthy White whitening mouth rinse (WMR), 5-Cavex Bite&White whitening pen (WP) and 6- no treatment (Con). The microhardness (VHN), surface roughness (Ra) and color of the specimens were measured (T 0 ). The specimens were then subjected to whitening protocols for 14 days (T 1 ). followed by artificial saliva storage for 14 days (T 2 ). The measurements were repeated at T 1 and T 2 . The SBS test was done after the application of 35% phosphoric acid (Scotchbond Universal Etchant), followed by a universal adhesive (G-Premio Bond) and a micro hybrid/universal resin composite (Essentia) into a Teflon tube attached to the enamel surface (p<0.05). Surface morphologies of the enamel surfaces were examined by SEM. p value was set at 0.05 Results Application of OP, PT and WP decrased the microhardness of enamel specimens (p<0.05) whereas, no significant changes were seen in the microhardness of enamel specimens treated with WT and WMR (p>0.05). Ra values of enamel specimens increased with the application of OP, PT and WT (p<0.05); whereas no changes were observed after the applications of WMR and WP (p>0.05). OP, PT, WMR, and WP changed the color of the enamel(p<0.05). There were not any significant differences among the SBSs of the groups, apart from OP applied enamel specimens. OP showed the least SBS values (p=0.001). SEM observations revealed smooth enamel surfaces. Conclusions: The whitening products affected the microhardness, surface roughness, color of enamel differently. Only OP decreased the SBS of the enamel.